Media filter fouling assessment using optical coherence tomography: New methodology. (April 2021) - Duran-Ros, Miquel; Solé-Torres, Carles; Ait-Mouheb, Nassim; Molle, Bruno; Arbat, Gerard; Puig-Bargués, Jaume
Abstract : Drip irrigation is an efficient and safe system for reusing wastewater in agriculture. Since emitter clogging is its main limitation, filtration is needed for preventing it. Media filters are commonly used when irrigation water has a high particle load. However, particle removal through a media bed in media filters used in drip irrigation systems has not been widely studied mainly due to experimental difficulties. To overcome this issue a new methodology using optical coherence tomography (OCT) is presented here. Experiments were carried out on a media filter at laboratory scale using wastewater. Once the filter was clogged, several 20 mm slices were taken and the retained total suspended solids were analysed by gravimetry. Following this, particles retained at six different locations of each slice were also determined using OCT. Results show a good agreement between total suspended solids experimentally determined and particles determined with OCT, especially when pixels attributed to particles were 30–45% of the total. Therefore, OCT could be a useful technique for assessing particle retention at different media depths. Highlights: Particle retention at different depths on media filters was studied in the laboratory. Optical coherence tomography (OCT) was used. OCT is a promising technique for analysing particle removal in media filters.